Enhancing reliability and safety in standalone or hybrid hydroelectric-wind energy systems: Failure events and safety barriers - Nasser Reem; Liu Yiliu (E3S Web of Conferences)
The reliability and safety of low-carbon energy systems, particularly hydroelectric and wind energy, are critical concerns given their increasing adoption and inherent failure risks. This study examines failure events in standalone and hybrid hydroelectric-wind systems, emphasizing the role of safety barriers in mitigating hazards. Failures in these systems can be categorized as detectable or undetectable, with undetectable failures posing significant risks due to delayed identification and intervention. The detectability of failures in each scenario has been assessed based on the difficulty associated with identifying the issue using existing technologies. In hydroelectric systems, critical failure scenarios include dam foundation settling, spillway gate malfunctions, turbine breakdowns, and drainage system blockages. For wind energy systems, common failure events involve blade damage, runaway events, lubrication system failures leading to fires, and tower instability. This work evaluates existing safety barriers and proposes improvements based on vulnerabilities identified in the literature, contributing to advancements in failure prevention and risk mitigation for renewable energy infrastructure.